Does Independent Directors Earn Higher Compensation? - Robin Robin; Claudio Esmeraldo Winarno (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
This study aimed to explore the effect of independent directors of a publicly listed company in indonesia on their total compensation. Following the footsteps of other developing countries, Indonesian corporations have recently appointed more independent directors. Independent directors are thought to play an important role in determining executive compensation. This Paper takes a sample of 50 publicly listed company in Indonesia ranked as the “best of the best company in 2020” by well known business magazine, Forbes. Those 50 companies were filtered by its financial performance and their practice of good corporate governance. 50 Financial reports spanning from the year 2015 – 2019 listed in the list were collected to analyze the relation ship between the number of independent director and total compensation recieved. The results of the studies suggest that the number of independent director does have an effect on their total compensation received. There is a significant positive relationship between the number of independent directors in a board structure and their total compensation received as indicated in both t-test and f-test of this study